Purification of Arabinoxylans from corn fiber and preparation of bioactive films for food packaging - Serra, Maria (2020)
Corn fiber, a by-product of the starch industry, is presently incorporated in animal feed. However, it has arabinoxylans as added-value components (besides ferulic acid) that should be valorized. In this work, the raw material, a fraction enriched in arabinoxylans from corn fiber, previously produced by alkaline extraction from corn fiber and pre-concentrated by ultrafiltration, was further purified. The use of ultrafiltration operated in diafiltration mode (dia-ultrafiltration) was evaluated for the purification of the arabinoxylans fraction. The objective was to maximize the removal of the small contaminants from the fraction and to maximize the permeability and/or the permeate flux, by selecting the relevant operating conditions involved in this process. The removal of contaminants (%) was estimated when their apparent rejection stabilized. Edible films were produced, from the resultant purified arabinoxylans fraction, using glycerol as plasticizer (30% dry basis). Additionally, films with the incorporation of ferulic acid were developed, in order to obtain barriers with antioxidant activity. The films were characterized in terms of mechanical properties, antioxidant activity and permeability to water vapor. The films prepared presented a good potential to be used as packaging for food products with low water content